2021
DOI: 10.1111/all.14787
|View full text |Cite
|
Sign up to set email alerts
|

Childhood asthma outcomes during the COVID‐19 pandemic: Findings from the PeARL multi‐national cohort

Abstract: Background The interplay between COVID‐19 pandemic and asthma in children is still unclear. We evaluated the impact of COVID‐19 pandemic on childhood asthma outcomes. Methods The PeARL multinational cohort included 1,054 children with asthma and 505 non‐asthmatic children aged between 4 and 18 years from 25 pediatric departments, from 15 countries globally. We compared the frequency of acute respiratory and febrile presentations during the first wave of the COVID‐19 pan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 42 publications
(82 reference statements)
2
62
0
1
Order By: Relevance
“…The PeARL study reported decreased incidence of upper and lower respiratory infections and febrile episodes among children with and without asthma, suggesting that decreased infectious triggers could play a role in improved asthma outcomes. 24 Supporting the potential role of decreased respiratory infections, a single center study of children with asthma reported the absence of the typical fall seasonal spike in asthma exacerbations that has been attributed to increased circulation of common respiratory viruses associated with schools reopening, as well as increased exposure to indoor allergens, changes in outdoor allergens, and colder weather. 25 While we did not have access to data on incidence of respiratory infections, we did find a decrease in prescriptions for antibiotics commonly prescribed for respiratory infections, suggesting decreased infections in our study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PeARL study reported decreased incidence of upper and lower respiratory infections and febrile episodes among children with and without asthma, suggesting that decreased infectious triggers could play a role in improved asthma outcomes. 24 Supporting the potential role of decreased respiratory infections, a single center study of children with asthma reported the absence of the typical fall seasonal spike in asthma exacerbations that has been attributed to increased circulation of common respiratory viruses associated with schools reopening, as well as increased exposure to indoor allergens, changes in outdoor allergens, and colder weather. 25 While we did not have access to data on incidence of respiratory infections, we did find a decrease in prescriptions for antibiotics commonly prescribed for respiratory infections, suggesting decreased infections in our study population.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Another retrospective analysis using data from 1054 children with asthma and 505 non‐asthmatic children in the multinational Pediatric Asthma in Real Life (PeARL) cohort identified decreased asthma‐related hospitalizations and emergency department visits and improved scores on validated asthma control measures, though there was an increase in the frequency of treatment escalation. 24 …”
Section: Discussionmentioning
confidence: 99%
“…As reported in other studies, social distancing and stepped-up hygiene measures determined a concomitant reduction in the diffusion of respiratory pathogens, leading to decreased respiratory tract infections 3,[25][26][27] . Moreover, the feeling of the emergency period might have enhanced adherence to controller medications among asthmatic population 27,28 .…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, other comorbidities, such as asthma [75][76][77], urticaria and erythema nodosum [78] have been associated with decreased risk of adverse COVID-19 outcome. However, these diseases often affect younger people, who are anyway less prone to COVID-19 adverse outcomes, and therefore, the observed protective effect might be the result of confounding [69].…”
Section: Comorbiditiesmentioning
confidence: 99%